SOME RESULTS OF THE U CrB OBSERVATIONS IN 1856 - 2007 - Grigorenko, V. D.; Gadon, S. A.; Shurpakov, S. E.; Bryukhanov, I. S. (Одеські астрономічні публікації, 2017)
Historical results over of photometry of eclipsing variable star U CrB (type of EA / SD) are brought after 1856 - 2007. Authors suppose that in the system U CrB there is a trade-out by a substance between components.